Dbl2 interacts with helicases and an endonuclease to maintain the integrity of repetitive regions - Anetta Bakosova; Lubos Cipak; Nina Mayerova; Kamil Krol; Zsigmond Benko; Alexandra Pitelova; Peter Kolesar; Dominika Piatrova; Maria Smondrkova; Anna Maresova; Lucia Molnarova; Ingrid Cipakova; et al. (Scientific Reports)
Abstract Helicases and endonucleases play crucial roles in genome maintenance by unwinding or cleaving various forms of DNA and RNA structures in order to facilitate essential biological processes, such as DNA replication and recombination. Here, we identified fission yeast Dbl2 as a potential interactor of several complexes that exhibit either helicase or endonuclease activity, namely Fml1-MHF, SCFFbh1, Rqh1-Top3-Rmi1, and Mus81-Eme1. In vitro, Dbl2 binds to DNA, with a preference for branched molecules, such as D-loops, mobile Holliday junctions, and fork structures, making it a good candidate to play a central role in modulating the activity of helicases and endonucleases during replication and recombination repair. Previously, we showed that Dbl2 recruits Fbh1 to the ongoing homologous recombination sites, affecting the Rad51-nucleofilament. In this study, we determined that deleting dbl2 in an fbh1Δ background did not increase sensitivity to DNA-damaging agents or the frequency of Tf2 ectopic recombination. Therefore, Dbl2 and Fbh1 might be involved in the same molecular pathway, maintaining genome integrity by hindering ectopic recombination at repetitive elements.